Containing an epidemic in the case of running out of treatment: A switched system approach - Salwahan, Shraddha; Abbas, Syed; Tridane, Abdessamad (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, we discuss an epidemic switched system. A susceptible–infected–treated model is considered. The course of an epidemic is profoundly influenced by the allocation of resources. If these resources are limited, then we need to devise an optimal distribution strategy. One significant case to study is when the drug supply is insufficient. We study a control problem that minimizes the total outbreak size of the epidemic and optimizes the rate of vaccination/isolation control by minimizing the suitable functional subject to resource constraints. In the end, simulations are performed for illustrations.
Keywords: switched system; epidemic model; optimal control